FRI0016 Involvement of runx-2 and β-catenin signaling in the production of adamts-7 and adamts-12 in osteoarthritic synovial fibroblasts. (15th June 2017) - Pérez-García, S; Gutiérrez-Cañas, I; Villanueva-Romero, R; Leceta, J; Fernández, J; González-Άlvaro, I; Juarranz, Y; Gomariz, RP
Abstract : Background: Proteinases released from synovial membrane of osteoarthritis (OA) patients contribute to cartilage damage. We recently reported in synovial fibroblasts (SF) the expression of ADAMTS (a disintegrin and metalloproteinase domain with thrombospondin motifs)-7 and -12, involved in the destruction of the cartilage oligomeric matrix protein (COMP) (1). Signaling pathways regulating these ADAMTS are poorly understood. As Runx2 and β-catenin are two transcription factors involved in chondrocytes metabolism and OA pathology (2–5), we studied whether these factors are implicated in the production of ADAMTS-7 and 12 in SF. Moreover, we analyzed the induction by two inflammatory mediators present in OA joints: interleukin-1β (IL-1β), and fibronectin fragments (Fn-fs), previously described in ADAMTS expression (1). Objectives: To elucidate the signaling pathways involved in the production of ADAMTS-7 and -12 in healthy donors (HD) - and OA-SF. Methods: ADAMTS-7 and -12 were detected in HD- and OA-SF protein extracts by Western blot. Blockade experiments were performed after stimulation with IL-1β or 45-kDa Fn-fs. We used inhibitors for two mitogen-activated protein kinases (MAPKs), ERK and p38, implicated in the activation of Runx2, PD98059 and SB203580, respectively. We also used an inhibitor of Wnt/β-catenin signaling, DDK-1. Levels of ADAMTS-7 and -12 were analyzed by quantitative RT-PCR and ELISA in SF culture supernatants. Results: Intracellular presence of ADAMTS-7 and -12 was confirmed in HD- and OA-SF, with higher levels of ADAMTS-7 in OA. After IL-1β or Fn-Fs stimulation, DDK-1 decreased ADAMTS-7 transcript in HD and OA-SF that was translated to a protein reduction in OA. Besides, ERK inhibitor decreased ADAMTS-12 mRNA and protein exclusively in OA-SF. Conclusions: We reported that ADAMTS-7 protein expression is higher in OA-SF compared to HD confirming previous data at mRNA level (1). As DKK decreased ADAMTS-7, Wnt-β-catenin signaling seems to be implicated in its expression. By contrast, the expression of ADAMTS-12 is regulated by ERK, pointing to a possible implication of ERK-Runx2 axis, exclusively in OA-SF. References: Pérez-Garcia S, Gutiérrez-Cañas I, Seoane IV, et al. Am J Pathol. 2016;186(9):2449–61. Yuasa T, Otani T, Koike T, et al. Laboratory Investigation. 2008;88(3):264–74. Luyten FP, Tylzanowski P, Lories RJ. Bone. 2009;44(4):522–7. Ji Q, Xu X, Xu Y, Fan Z, Kang L, Li L, et al. J Mol Med (Berl). 2016;94(6):681–94. Komori T. Cell and tissue research. 2010;339(1):189–95. Acknowledgements: This work has been supported by Instituto de Salud Carlos III, Spain, cofinanced by FEDER, European Union: RETICS program, Red de Investigaciόn en Inflamaciόn y Enfermedades Reumáticas (RD16/0012/0008 (RPG) and RD16/0012/0011 (IGA) and the projects PI12/00758 (RPG), PI14/00477 (CMM) and PI14/00442 (IGA). Disclosure of Interest: None declared